IKKα inibition by a glucosamine derivative enhances Maspin expression in osteosarcoma cell line. (25th January 2017) - Leopizzi, Martina; Cocchiola, Rossana; Milanetti, Edoardo; Raimondo, Domenico; Politi, Laura; Giordano, Cesare; Scandurra, Roberto; Scotto d'Abusco, Anna
Abstract: Chronic inflammation has been associated to cancer development by the alteration of several inflammatory pathways, such as Nuclear Factor-κB pathway. In particular, IκB kinase α (IKKα), one of two catalytic subunit of IKK complex, has been described to be associated to cancer progression and metastasis in a number of cancers. The molecular mechanism by which IKKα affects cancer progression is not yet completely clarified, anyway an association between IKKα and the expression of Maspin (Mammary Serine Protease Inhibitor or SerpinB5), a tumor suppressor protein, has been described. IKKα shuttles between cytoplasm and nucleus, and when is localized into the nuclei, IKKα regulates the expression of several genes, among them Maspin gene, whose expression is repressed by high amount of nuclear IKKα. Considering that high levels of Maspin have been associated with reduced metastatic progression, it could be hypothesized that the repression of IKKα nuclear translocation could be associated with the repression of metastatic phenotype. The present study is aimed to explore the ability of a glucosamine derivative, 2-( N -Carbobenzyloxy)l -phenylalanylamido-2-deoxy-β-d -glucose (NCPA), synthesized in our laboratory, to stimulate the production of Maspin in an osteosarcoma cell line, 143B. Immunofluorescence and Western blotting experiments showed that NCPA is able to inhibit IKKα nuclear translocation, and to stimulate Maspin production. Moreover, in association with stimulation of Maspin production we found the decrease of β1 Integrin expression, the down-regulation of metalloproteases MMP-9 and MMP-13 production and cell migration inhibition. Taking in account that β1 Integrin and MMP-9 and -13 have been correlated with the invasiveness of osteosarcoma, considering that NCPA affects the invasiveness of 143B cell line, we suggest that this molecule could affect the osteosarcoma metastatic ability. Graphical abstract: Highlights: NCPA is a glucosamine derivative able to counteract inflammatory pathways. NCPA inhibits IKKα nuclear translocation inducing Maspin production. NCPA decrease β1 Integrin and MMP-9 and -13. NCPA inhibits cell migration in osteosarcoma cell line 143B.